Effect of Cardiac Rehabilitation on Anxiety and Depression in CABG Patients - Farkhondeh Sharif; Ali Reza Shoul; Mansour Jannati; Najaf Zare; Javad Kojouri (University of Social Welfare and Rehabilitation Sciences, 2011)
Objective: Many patients experience with anxiety and depression after cardiac bypass surgery as a consequence of this type of surgery. The aim of this study was to examine the effect of cardiac rehabilitation on anxiety and depression level of patients undergoing Coronary Artery Bypass Graft Surgery in hospitals affiliated to Shiraz University of Medical Sciences. Materials & Methods: In this interventional study 80 randomly patients, based on convenience sampling, who had the required criteria were selected and divided into two groups marked as experimental and control groups. The data were collected using three questionnaires. Demographic questioner and The Spielberger anxiety scale for measuring the state and trait of anxiety and the Beck depression inventory for measuring the depression. Both groups answered these questionnaires in three stages: on discharge from hospital , immediately and two months after cardiac rehabilitation. After measuring anxiety and depression in both groups on discharge the experimental group participated in 8 session cardiac rehabilitation in four weeks. The control group received only routine program. The data was analyzed using t-test, repeated measurement multi-variate test, chi square, regression analysis and correlation coefficient. Results: The results revealed that after cardiac rehabilitation program there was a significant statistical differences in depression level between groups (P=0.0014) but in anxiety level, there was no statistical significant difference (P=0.079) between groups. Conclusion: Cardiac rehabilitation is effective in reducing depression in patients undergoing Coronary Artery Bypass Graft Surgery. Therefore it is recommended to use cardiac rehabilitation in these patients.